Simulation Analysis of Riveted Joint Specimen with Parameter of Working Pressure and Hole Clearance Using Semi-Automatic Riveting Tool - Galang Saputro; Muhammad Akhlis Rizza; Utsman Syah Amrullah (Asian Journal Science and Engineering, 2023)
Squeeze force, rivet length, rivet diameter, and hole clearance are the factors that affect the riveting procedure and the effectiveness or result of the rivets. In this riveting simulation, the riveting parameters are determined using a semi-automatic riveting tool. The semi-automatic riveting tool's working pressure is the parameter set, and the hole clearance is created during the drilling process on sheet metal. The results of riveting simulation show that the working pressure of the rivet gun and the hole clearance directly impact the rivets' shear strength. The shear strength of the rivets will increase with higher operating pressure of the rivet gun and larger hole clearance. Due to the strain hardening that occurs when rivets are hit with a rivet gun during the riveting process, the shear strength of rivets has increased. Keywords: Rivet Gun Pressure, Hole Clearance, Shear Strength